Design and Development of a Web-Based Internal Service Disruption Information System at PT. Kereta Api Indonesia Divre I North Sumatra - Agustiani Hotmaida Br Siahaan (Journal Majelis Paspama, 2024)
This study aims to design and develop a Web-Based Internal Service Disruption Information System at PT. Kereta Api Indonesia (Persero) Divre I North Sumatra. The main problem faced is the manual process of submitting complaints between departments, which is inefficient and time-consuming. The web-based system is expected to simplify the process of reporting service disruptions quickly and in a structured manner without requiring employees to visit the relevant department directly. The research methods used include interviews, observations, and field research to collect relevant data regarding the internal complaint process within the company. The system was developed using Macromedia Dreamweaver CS3 and PHP MyAdmin, supported by the necessary hardware and human resources capable of operating the system. The implementation results show that the designed system can facilitate the process of submitting and handling internal complaints more efficiently. With a simple user interface and features such as complaint input, response management, operator data, and reporting, the system improves communication effectiveness and accelerates service disruption handling.Therefore, this information system can serve as a digital solution to support the improvement of internal service quality at PT. Kereta Api Indonesia Divre I North Sumatra.